Workforce Unit Abstraction for Governing Hybrid Human and Artificial Intelligence Operations - Gopal Yuvaraj (Malikussaleh University, Aceh, Indonesia, 2026)
Enterprise service organizations increasingly deploy artificial intelligence agents alongside human workers. Yet, incumbent workforce management frameworks remain anchored to a purely human labor model, rendering AI agents invisible to capacity planning, performance attribution, and governance enforcement. This article addresses that conceptual gap through a design science research methodology, introducing three constructs as reusable primitives for hybrid workforce platform design. The Workforce Unit Abstraction defines a unified seven-attribute operational schema applicable to both human workers and AI agents, enabling consistent representation across planning, scheduling, and governance systems. The Hybrid Capacity Model extends demand-to-supply planning across heterogeneous workforce pools, resolving a multi-objective allocation problem that simultaneously optimizes cost, quality, and risk constraints. Governance-bound autonomy constrains AI Workforce Unit actions within a five-level, policy-enforced autonomy ladder supported by six mandatory governance controls. Together, these constructs provide a coherent reference model that closes the documented gaps in hybrid workforce management, including scheduling inefficiencies of up to 28%, attribution failures in 68% of organizations, and governance ambiguity responsible for 61% of hybrid workflow failures. The framework establishes a principled vocabulary for designing enterprise service platforms that manage human and artificial intelligence labor responsibly, transparently, and at scale.